196k views
4 votes
The polynomial p(x)=3x^3-20x^2+37x-20 has a known factor of (x-4). Rewrite p(x) as a product of linear factors. p(x) =

User Jirimertin
by
4.4k points

2 Answers

3 votes

Answer: (x-4)(3x-5)(x-1)

Explanation:

User Rieko
by
4.8k points
9 votes

Answer:


p(x) = (x-4)(x - (5)/(3))(x - 1)

Explanation:

Solving a quadratic equation:

Given a second order polynomial expressed by the following equation:


ax^(2) + bx + c, a\\eq0.

This polynomial has roots
x_(1), x_(2) such that
ax^(2) + bx + c = a(x - x_(1))*(x - x_(2)), given by the following formulas:


x_(1) = (-b + √(\bigtriangleup))/(2*a)


x_(2) = (-b - √(\bigtriangleup))/(2*a)


\bigtriangleup = b^(2) - 4ac

In this question:

We have the polynomial
p(x) = 3x^3-20x^2+37x-20

It has a known factor
x - 4. This means that the polynomial can be written as:


p(x) = (x-4)q(x)

In which q(x) is a second order polynomial, because p is of the third degree and q is of the first degree(3 - 1 = 2). So


q(x) = ax^2 + bx + c

We have to find a, b and c. Then


3x^3-20x^2+37x-20 = (x-4)(ax^2 + bx + c)


3x^3-20x^2+37x-20 = = ax^3 + (-4a + b)x^2 + (c - 4b)x - 4c

Comparing both sides, we have that


a = 3


-4c = -20 \rightarrow c = 5


c - 4b = 37


-4b = 32 \rightarrow b = -8

Now we find the roots of this polynomial.


\bigtriangleup = b^(2) - 4ac = (-8)^2 - 4(3)(5) = 64 - 60 = 4


x_(1) = (-(-8) + √(4))/(2*3) = (5)/(3)


x_(2) = (-(-8) - √(4))/(2*3) = 1

So, as a product of it's factors, we have that q is:


q(x) = (x - (5)/(3))(x - 1)

And p(x)


p(x) = (x-4)q(x)


p(x) = (x-4)(x - (5)/(3))(x - 1)

User Nothehi
by
4.6k points